2022
DOI: 10.3390/ijerph192315604
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Associations between Physical Activity and Sleep Duration in Relation to Adolescent Academic Achievement

Abstract: Purpose: The present study aimed to examine independent and interactive associations between physical activity and sleep duration with adolescent academic achievement. Methods: This cross-sectional study used data from the 2019 cycle of the US-based Youth Risk Behavior Surveillance System. A total of 13,677 American adolescents in grades 9 through 12 (MAGE = 16.06 ± 1.24 years; 50.9% female) self-reported their sleep and physical activity behavior as well as their grades. Linear regression models fit with cubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This inadequacy translates into low levels of PA in school-aged children and adolescents (Global Matrix, GM 2.0; GM 3.0). Furthermore, for young people, the indicated state is not improved by the progressive access to electronic devices, which may be conducive to a sedentary lifestyle and, consequently, negatively affect their cognitive development and lower school achievement, as indicated in studies conducted by other researchers [ 22 ]. For this reason, given the current state of knowledge, our study aimed to investigate how PA, screen time, and sleep duration influence the level of school competence among young individuals of both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inadequacy translates into low levels of PA in school-aged children and adolescents (Global Matrix, GM 2.0; GM 3.0). Furthermore, for young people, the indicated state is not improved by the progressive access to electronic devices, which may be conducive to a sedentary lifestyle and, consequently, negatively affect their cognitive development and lower school achievement, as indicated in studies conducted by other researchers [ 22 ]. For this reason, given the current state of knowledge, our study aimed to investigate how PA, screen time, and sleep duration influence the level of school competence among young individuals of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dewald et al [ 21 ] found strong associations between three sleep variables [sleep quality ( r = 0.096), duration ( r = 0.069), and sleepiness ( r = -0.133)] and school performance, especially in boys. Yet, Brown et al [ 22 ], analysing risky behaviours in a sample of 13,677 American adolescents in grades 9 through 12, discovered significant curvilinear relationships between PA, sleep, and academic achievement. Optimal grades were associated with 7–9h of sleep per night and 5–7h of PA per week.…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, sufficient sleep and physical fitness. The extent of existing organismic capital (e.g., sleep patterns and physical activities) shows correlations to performance already in the early phase of talent development 86 and gains further importance in the course of talent development due to increasingly extensive learning processes 87 . The same applies to attentional learning capital , which refers to the quantitative and qualitative attentional resources a person can direct toward learning.…”
Section: Resources For Talent Development Toward Excellence and Innov...mentioning
confidence: 99%